Pengaruh Bimbingan Guru PAK dan Budi Pekerti Terhadap Peningkatan Disiplin Belajar Siswa Kelas V SD Negeri 048232 Kabupaten Karo Tahun Pembelajaran 2023/2024 - Morina Octavianty Pane; Junjungan Simorangkir; Risden Anakampun (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to find out how big the influence of PAK Teacher Guidance and Characteristics is on the learning discipline of class V students at SD Negeri 048232 Karo Regency for the 2023/2024 Academic Year. The research method used is a quantitative method. The population is all class V students of SD Negeri 048232 Karo Regency for the 2023/2024 academic year, totaling 39 people and this research is population research. Data was collected using a positive closed questionnaire with 30 items, namely 17 items for variable Karo Regency for the 2023/2024 Academic Year, proven through: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.665 > rtable (-0.05.39) = 0.316. b) The significant relationship test obtained a t0 value of 5.413 ttable (0-0.05, den-2-37) 2.021. 2) Influence test: a) Regression equation test, obtained regression equation Y = 17.881 + 0.219X. b) Regression coefficient of determination test (r²) = 44.2%. 3) Hypothesis testing using the F test obtained F0 > Ftable (0-0.05, in the numerator k30, dk in the denominator-2-39-2-37) namely 29.30 1.51. Thus Ha is accepted and Ho is rejected.